Diversity of Butterfly Species in The Kerandangan Nature Tourism Park, Senggigi, West Lombok - Rita Alawiyah; Norma Azizah; Lalu Ahmad Azfani; Siti Diniah; Intan Putri Yasa; Maulidatin Nanisfi; Reginah Fhatonah Insani; Habibah Habibah; Masnayati Hilmi; Vines Salsa Imami (Journal of Biology, Environment, and Edu-Tourism, 2025)
The potential of biodiversity owned by Nature Tourism Park Kerandangan is very large and has not been studied in depth, one of which is the potential for butterfly diversity. Butterflies are animals from the insect group that have special characteristics of wings consisting or composed of scales. The method we used during butterfly observations was the explorative survey method by selecting certain areas as stations. With a sampling technique using purposive sampling, namely a deliberate sampling technique according to the required sample requirements. In the results of this butterfly diversity observation using the Shannon-Wiener diversity formula. With the number of individual butterflies in each block, namely the intensive use block with a total of 138, the limited use block with 79 individuals, the protection block with 55 individuals, and the rehabilitation block with 58 individuals. The results of this study indicate that Nature Tourism Park Kerandangan has a high potential for butterfly diversity, especially in the intensive use block, which indicates the importance of this area as a natural habitat that needs to be managed properly to maintain ecosystem balance. It is recommended that further, more in-depth and comprehensive research be conducted on biodiversity throughout the Kerandangan Nature Tourism Park area block, as well as the implementation of appropriate conservation strategies to protect butterfly species and increase public awareness of the importance of biodiversity conservation.